Large kidneys predict poor renal outcome in subjects with diabetes and chronic kidney disease - Rigalleau, Vincent; Garcia, Magalie; Lasseur, Catherine; Laurent, François; Montaudon, Michel; Raffaitin, Christelle; Barthe, Nicole; Beauvieux, Marie-Christine; Vendrely, Benoit; Chauveau, Philippe; Combe, Christian; Gin, Henri (BMC nephrology, 2010)
Background Renal hypertrophy occurs early in diabetic nephropathy, its later value is unknown. Do large kidneys still predict poor outcome in patients with diabetes and Chronic Kidney Disease (CKD)? Methods Seventy-five patients with diabetes and CKD according to a Glomerular Filtration Rate (GFR, by 51Cr-EDTA clearance) below 60 mL/min/1.73 m 2 or an Albumin Excretion Rate above 30 mg/24 H, had an ultrasound imaging of the kidneys and were cooperatively followed during five years by the Diabetology and Nephrology departments of the Centre Hospitalier Universitaire de Bordeaux. Results The patients were mainly men (44/75), aged 62 ± 13 yrs, with long-standing diabetes (duration:17 ± 9 yrs, 55/75 type 2), and CKD: initial GFR: 56.5 (8.5-209) mL/min/1.73 m 2 , AER: 196 (20-2358) mg/24 H. Their mean kidney lenght (108 ± 13 mm, 67-147) was correlated to the GFR (r = 0.23, p < 0.05). During the follow-up, 9/11 of the patients who had to start dialysis came from the half with the largest kidneys (LogRank: p < 0.05), despite a 40% higher initial isotopic GFR. Serum creatinine were initially lower (Small kidneys: 125 (79-320) μmol/L, Large: 103 (50-371), p < 0.05), but significantly increased in the "large kidneys" group at the end of the follow-up (Small kidneys: 129 (69-283) μmol/L, Large: 140 (50-952), p < 0.005 vs initial). The difference persisted in the patients with severe renal failure (KDOQI stages 4,5). Conclusions Large kidneys still predict progression in advanced CKD complicating diabetes. In these patients, ultrasound imaging not only excludes obstructive renal disease, but also provides information on the progression of the renal disease.